ANALYSIS OF TEACHERS ABILITY IN LEARNING IPAS IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Nada Wulandari; Mustafa; Ali latif (Media Inovasi Pendidikan dan Publikasi, 2024)
This research examines the analysis of teachers' abilities in science and science learning in the implementation of the Merdeka Curriculum. The focus studied in this research is: (1) What are the teachers' abilities in learning science and technology (2) constraints and barriers to learning science and technology in the independent curriculum?, (3) efforts to overcome obstacles to learning science and technology in the independent curriculum. The objectives of this research are: (1) What are the teacher's abilities in learning science and technology, (3) obstacles and barriers to learning science and technology in the independent curriculum, (4) efforts to overcome obstacles and obstacles in the independent curriculum. The focus of this research is class III, IV, V and IV teachers. Data collection techniques are observation, interviews and documentation. The research results show that: (1) The implementation of the independent curriculum in science and science learning has been carried out well. The teacher has prepared teaching modules based on CP, TP and ATP. (2) there are still obstacles and barriers, there are some teachers who do not understand how to implement the independent curriculum, lack of time in creating teaching modules, and there is still a lack of facilities and infrastructure in the classroom. (3) overcoming obstacles by taking part in a workshop regarding the independent curriculum and participating in the KKG